Lithium ion battery applications of molybdenum disulfide (MoS2) nanocomposites - Stephenson, T; Li, Z; Olsen, B; Mitlin, D (Energy & environmental science, 2014)
This is the first targeted review of the synthesis-microstructure- electrochemical performance relations of MoS2-based anodes and cathodes for secondary lithium ion batteries (LIBs). Molybdenum disulfide is a highly promising material for LIBs that compensates for its intermediate insertion voltage (∼2 V vs. Li/Li+) with a high reversible capacity (up to 1290 mA h g-1) and an excellent rate capability (e.g. 554 mA h g-1 after 20 cycles at 50 C). Several themes emerge when surveying the scientific literature on the subject: first, we argue that there is excellent data to show that truly nanoscale structures, which often contain a nanodispersed carbon phase, consistently possess superior charge storage capacity and cycling performance. We provide several hypotheses regarding why the measured capacities in such architectures are well above the theoretical predictions of the known MoS2 intercalation and conversion reactions. Second, we highlight the growing microstructural and electrochemical evidence that the layered MoS2 structure does not survive past the initial lithiation cycle, and that subsequently the electrochemically active material is actually elemental sulfur. Third, we show that certain synthesis techniques are consistently demonstrated to be the most promising for battery applications, and describe these in detail. Fourth, we present our selection of synthesis methods that we believe to have a high potential for creating improved MoS 2 LIB electrodes, but are yet to be tried. This journal is © 2014 The Royal Society of Chemistry.